Respuesta :

♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️

[tex] \frac{43}{10} - x = 4 \\ [/tex]

[tex] \frac{43}{10} - x = \frac{40}{10} \\ [/tex]

Subtract sides 43 / 10

[tex] - \frac{43}{10} + \frac{43}{10} - x = - \frac{43}{10} + \frac{40}{10} \\ [/tex]

[tex] - x = \frac{ - 43 + 40}{10} \\ [/tex]

[tex] - x = - \frac{3}{10} \\ [/tex]

Negatives simplifies

[tex]x = \frac{3}{10} \\ [/tex]

♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️

Thus we need to subtract

[tex] \frac{3}{10} \\ [/tex]

♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️

Answer:

83/10

Step-by-step explanation:

let x represent the number:

43/10 - x = 4

x = 4 + 43/10

simplifying the answer:

x = (4(10) + 43)/10

x = (40 + 43)/10

x = 83/10